Cherishing the memories you have Practices of place care and remembrance in contemporary Nowa Huta - Malmgren, Agnes ; 0000-0003-3541-6500 (Zeitschrift fur Slawistik, 2025)
In recent years, there has been a growing scholarly interest in the cultural and political significance of joyful, positive and nostalgic memories and forms of remembrance. Without downplaying the role of trauma and oppression in the mnemonic makeup of contemporary societies, memory scholars have increasingly pointed to the co-existence, or parallel existence, of brighter recollections of the past, and to their role in bringing about hope and social mobilization (Katriel & Reading 2015; Keightley & Pickering 2012; Rigney 2018; Sindbæk Andersen & Ortner 2019). Engaging with these streams of thought, my article will offer a closer look at the interplay between memories of friendship and mutual care, and remembrance as a form of caring (Till 2012), which enables the continuation and/or formation of solidaric bonds, practices, and ideas. Empirically, the article departs from Nowa Huta, a district in Kraków, which was founded in 1949 as the "first socialist town in Poland", and which eventually, in the 1980 s, turned into one of the main bastions of the oppositional Solidarity movement. After 1989, Nowa Huta became fertile ground for memory work of different kinds: commemorations, exhibitions, nostalgic venues and paraphernalia, along with numerous heated debates on the matter of remembrance. While divisive in the public sphere, memory has simultaneously served as a creative and cohesive force for many of the local communities, of different orientation, which put their mark on contemporary Nowa Huta. Drawing on ethnographic field work, my article will illustrate the role of memory in sustaining care and friendship within a few of these communities. It will also show the wider entanglements of these communal memories; how they relate and sometimes serve as corrections to diverging representations of the past and how they move from their 'original' confines to a younger generation of locally involved inhabitants in Nowa Huta. In that way, they function as a kind of springboard, a resource, for continuous place-based caring and solidaric action within and for the neighborhood.
Publisher Copyright: © 2025 the author(s), published by Walter de Gruyter GmbH, Berlin/Boston.
Keywords: (slow) memory; locality; nostalgia; Nowa Huta; place care; post socialism; solidarity